The Multiliteration Learning Model on Narrative Writing Skills in Elementary School - Rayen Septi Arwita; Jusmawati; Satriawati; Waddi Fatimah; Eka Fitriana H. S. (Universitas Pendidikan Ganesha, 2022)
Most students experienced low learning outcomes in learning to write narrative essays in learning Indonesian. It is because the model used by the teacher is still conventional. Learning activities are still teacher-centered, so student creativity needs to develop optimally. Therefore, a learning model is needed that can overcome students' problems in writing narrative essays. This study aims to analyze the effect of the multiliteracy learning model on narrative writing skills in grade V elementary school. This research is quantitative with the type of experimental research in the form of a pre-experimental one-group pretest-posttest design. The sample in this study was 27 students. The sampling technique uses simple random sampling. Observation, tests, and documentation carry out data collection techniques. Data were analyzed using descriptive and inferential statistical analysis with the help of the SPSS version 20 computer program. The results of this study indicate that the teacher's ability to apply the multiliteracy learning model means that it is well implemented. The learning outcomes of students' narrative writing skills in class VB, so the results of this study indicate an influence of the multiliteracy learning model on narrative writing skills in class V elementary school students. From the analysis results, the multiliteracy learning model has proven to affect narrative writing skills.